2020
DOI: 10.1200/po.20.00122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Leiomyosarcomas With Somatic Alteration in Homologous Recombination Pathway Genes

Abstract: PURPOSE To detect alterations in DNA damage repair (DDR) genes, measure homologous recombination deficiency (HRD), and correlate these findings with clinical outcome in patients with leiomyosarcoma (LMS). PATIENTS AND METHODS Patients with LMS treated at Memorial Sloan Kettering (MSK) Cancer Center who consented to prospective targeted next-generation sequencing with MSK-IMPACT were screened for oncogenic somatic variants in one of 33 DDR genes; where feasible, an experimental HRD score was calculated from IMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
(49 reference statements)
2
26
0
Order By: Relevance
“…The HR deficiency status can be assessed by checking the percentage of genomic regions with loss of heterozygosity (LOH) using single nucleotide polymorphism (SNP) sequencing or by calculation of the Genomic Instability Score (GIS) via coalescing three parameters: LOH, large scale transitions (LSTs) and telomeric allelic imbalance (TAI). Other assays such as the FDA-approved MSK-IMPACT, which provides integrated mutation profiling of actionable cancer targets developed by Memorial Sloan Kettering’s Department of Pathology, also cover detection of somatic variants in DDR genes and allow evaluation of experimental HR deficiency scores ( 63 , 64 ). Recently, HRDetect, a new computational method dedicated to measuring HR deficiency based on whole-genome sequencing (WGS) data, is gaining momentum as a predictor of PARPi response.…”
Section: Dna Damage Repair Pathways and Cancermentioning
confidence: 99%
“…The HR deficiency status can be assessed by checking the percentage of genomic regions with loss of heterozygosity (LOH) using single nucleotide polymorphism (SNP) sequencing or by calculation of the Genomic Instability Score (GIS) via coalescing three parameters: LOH, large scale transitions (LSTs) and telomeric allelic imbalance (TAI). Other assays such as the FDA-approved MSK-IMPACT, which provides integrated mutation profiling of actionable cancer targets developed by Memorial Sloan Kettering’s Department of Pathology, also cover detection of somatic variants in DDR genes and allow evaluation of experimental HR deficiency scores ( 63 , 64 ). Recently, HRDetect, a new computational method dedicated to measuring HR deficiency based on whole-genome sequencing (WGS) data, is gaining momentum as a predictor of PARPi response.…”
Section: Dna Damage Repair Pathways and Cancermentioning
confidence: 99%
“…The major biallelic inactivation of BRCA1 and/or BRCA2 in uLMS, which is one of the most proficient biomarkers for the response of poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors, is somatic homozygous deletion of BRCA2 , although germline pathogenic or likely pathogenic mutations, along with loss of heterozygosity (LOH), are major causes of biallelic inactivation of BRCA1/2 in other gynecologic malignancies, including ovarian cancer [ 49 ]. To date, the association between somatic BRCA1/2 variation in uLMS and ethnic-specificity has not been reported, but the prognosis of uLMS with loss of DNA repair-related genes was worse than that of uLMS without alterations in these genes [ 50 ].…”
Section: Homologous Recombination Deficiency In Ulmsmentioning
confidence: 99%
“…Homologous recombination deficiency (HRD), including the pathogenic mutation in BRCA2 , was frequently observed, and BRCA2 deletion was observed in 50% (hemizygous deletion 40%, homozygous deletion 10%) of cases in uLMS [ 51 ]. Moreover, mutations in the BRCA2 gene were observed more frequently in uLMS than in nuLMS (approximately 10% vs. 1%) [ 50 , 52 ]. In a study where a cancer genome profile test was conducted on 80 cases of uLMS, Hensley et al reported that homozygous deletions and truncating mutations in BRCA2 were observed in 5% and 2.5% of cases, respectively [ 32 ].…”
Section: Homologous Recombination Deficiency In Ulmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutically targetable somatic alterations were labeled using levels of clinical actionability defined in OncoKB, which range from level 1, FDA-recognized biomarkers of response to FDA-approved drugs, to level 4, biomarkers of hypothetical relevance based on compelling preclinical biological evidence. Analyses of alterations in oncogenic signaling pathways were performed using the set of pathway definitions previously curated by our group, which we expanded to include the DDR and epigenetic modifier pathways using additional templates curated from literature subtypes (24,(51)(52)(53).…”
Section: Computational Genomic Analysismentioning
confidence: 99%